Efficient oil-water separation by novel biodegradable all cellulose composite filter paper - Chizhou Wang; Shaodi Wu; Ning Zhang; Zhaoli Jiang; Xianglin Hou; Long Huang; Tiansheng Deng (Green Energy & Environment, 2023)
Industrial production and domestic discharge produce a large amount of oily wastewater, which seriously affects the stability of the ecological environment. Membrane separation technology provides another path to treating oily wastewater. And appropriate surface modification of the membrane helps to achieve high efficiency of treating oily wastewater. With green, economy and stability been more concerned. The focal research reports a completely biodegradable all cellulose composite filter paper (ACCFP) composed of I-cellulose macrofibers and II-cellulose matrix. It is a simple one-step impregnation method to adjust the surface microstructure of the pristine filter paper (PFP), and it does not involve with chemical reaction. The pre-wetted ACCFP consist of II-cellulose hydrogel and I-cellulose reinforcement in the process of oil-water separation. This layer of hydrogel is the fundamental to underwater superoleophobicity, which determines their eligibility for applications of efficient oil-water mixture or oil-in-water (oil/water) emulsion separation. The separation efficiency of oil-water mixture and oil/water emulsion exceed 95% and 99.9%, respectively. In addition, excellent mechanical properties of ACCFP in dry and wet conditions ensure its stability in service and prolong service life in applications. The focal study provides a new method for high-performance oil-water separation and it is more in line with sustainable chemistry.